MODERN SOCIAL DOCTRINE OF THE CONSTANTINOPLE PATRIARCHATE - Bogdan Gulyamov ("Scientific Information Agency "Science-technologies-information" LLC, 2020)
The theology of communication suggests looking at man as a being called to communion in general and to communion with God in particular, in God he sees the first Community of Communion, each Hypostasis of the Trinity exists exclusively in a relationship of mutual gift of existence. It has been studied that the church for the theology of communication must be a reflection of the Trinity, be the communication of the individual with God and with other people, the hierarchy only serves such communication, but cannot replace it. Human society must be a space for interpersonal communication, a community or a set of communities. It turns out that the social doctrine of the Ecumenical Patriarchate is consistent with the Christian realism of Richard Niebuhr, according to which all forms of government are far from the gospel ideal, but this does not prevent to distinguish relative evil from absolute evil.